Study of Carbon Nanotube–Bovine Serum Albumin Interaction Using the Tritium Radiotracer Technique and Supercomputer Simulation - Vitalii A. Bunyaev; Artem V. Sinolits; Gennadii A. Badun (Biology and life sciences forum, 2024)
Bovine serum albumin (BSA) was 3H-labeled via a tritium thermal activation method that allowed quantifying BSA adsorption on single-walled carbon nanotubes (SWCNTs) to be 740 mg/mg, which leads to the ζ-potential of the BSA–SWCNT complex changing from −10 to −16 mV. Supercomputer simulations were carried out with Gromacs and PM7 with MOPAC2016 with Berendsen, Nosè–Hoover and Parrinello–Rahman algorithms. The dominant interactions between BSA and SWCNTs are found to be hydrophobic, and hydrogen bonds are also present. The mean total energy of the Coulomb and Van der Waals interactions is −646 ± 8 kJ/mol, by gmx energy.